2022
DOI: 10.1186/s12904-022-01065-5
|View full text |Cite|
|
Sign up to set email alerts
|

Palliative care symptoms, concerns and well-being of older people with frailty and complex care needs upon hospital discharge: a cross-sectional study

Abstract: Background Little is known about the nature and intensity of palliative care needs of hospitalised older people. We aimed to describe the palliative care symptoms, concerns, and well-being of older people with frailty and complex care needs upon discharge from hospital to home, and to examine the relationship between palliative care symptoms and concerns, and well-being. Methods Cross-sectional study using baseline survey data of a pilot randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Studies identified were conducted in eight high-income countries and one upper middle-income country. These included the Netherlands, 21 , 24 , 26 , 27 , 30 , 31 USA, 23 , 28 , 33 UK, 25 , 32 Australia, 34 Belgium, 29 Canada, 22 Spain, 36 Sweden 35 and Brazil. 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies identified were conducted in eight high-income countries and one upper middle-income country. These included the Netherlands, 21 , 24 , 26 , 27 , 30 , 31 USA, 23 , 28 , 33 UK, 25 , 32 Australia, 34 Belgium, 29 Canada, 22 Spain, 36 Sweden 35 and Brazil. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Study settings were described as community care, 21 , 25 27 , 37 integrated care, 28 , 31 long term care, 34 36 acute care, 23 , 24 , 29 mixed community and acute settings 22 , 33 specialist palliative community care 32 and population level study. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was wellbeing at 2-4 weeks (T1), measured using the Integrated Palliative care Outcome Scale (IPOS) [ 10 ]. IPOS is a valid and reliable self-reported measure used to assess symptoms and other concerns (overall wellbeing) among those with advanced illness [ 10 ] and at risk of frailty [ 11 , 12 ]. It can be reported as a total score (17 items: scoring 0-68; higher scores indicating worse wellbeing), or subscales: physical subscale (10 items: scoring 0-40); psychological (4 items: scoring 0-16); communication/practical subscale (3 items: scoring 0-12) [ 10 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the author reported that Figs. 1 and 2 were not complete as submitted.…”
mentioning
confidence: 99%